Does by-catch pose a threat for the conservation of seabird populations in the southern Ionian Sea (eastern Mediterranean)? A questionnaire based survey of local fisheries - KARRIS, G.; FRIC, J.; KITSOU, Z.; KALFOPOULOU, J.; GIOKAS, S.; SFENTHOURAKIS, S.; POIRAZIDIS, K. (Mediterranean Marine Science, 2013)
A significant number of studies worldwide have shown that incidental catches (by-catch) of seabirds in fishing gear might pose a considerable risk for the conservation of their populations. Nevertheless reliable data on by-catch rates of seabirds in European marine ecosystems are patchy and need to be improved. This study constitutes a first attempt at the evaluation of by-catch rates in the southern Ionian Sea. Data were obtained by distributing a specific questionnaire to the fishers of Zakynthos Island. 150 professional fishers (representing 90% of the local fishing fleet) participated in the research, and were interviewed during July-December 2010. The information collected showed that commercial longline and (to a lesser extent) gillnet fishery gears caused incidental catches mostly of Scopoli’s Shearwater and Mediterranean Shag. The temporal analysis of the incidental bird mortality showed that seabirds were more susceptible to be trapped in fishery gears set around sunrise during spring and summer whereas spatial analysis of by-catch data indicated variations in the number of seabirds caught in different fishery areas.